Software para la enseñanza-aprendizaje del lenguaje en niños con síndrome de Down de la escuela "Mariano Negrete" - Quinga Nasimba, Mayra Valeria (2017)
Today the inclusion of ICTs in education has reduced learning barriers in children with special capacities, the hole training that the students receive in the classrooms is done by means of work cards which are designed on cardboards that have images and their meaning, these didactic resources must be carried out each school year because in handling them for a long time they deteriorate. With the development of the educational software will solve the problem previously described and is strengthen the process of teaching – language learning in children with Down syndrome directed of Initial II of "Mariano Negrete" School. To give a solution as mentioned above the bootstrap framework was used with the open source language PHP connected to the MySQL database with the integration of JavaScript and Jquery code that interact with HTML to create a dynamic software, text holder, event handling, animation, sounds, actions that are done by pressing buttons and finally windows with warning messages to the user. The methodology applied was of Brian Blum, consists of five phases like the analysis, the educational, the development of the stage of programming, the production where the sounds and animations are made and the evaluation where the tests are carried out, other important results were the functional and pedagogical requirements making that the software will be friendly and interact with the user setting goals and objectives being able to recognize the alphabet , animals, sounds, colors and numbers by developing their mental capacities.